Collaborative governance in the management of political violence in Bauchi State, Nigeria - Ilelah, Kabiru Bello; Ab Halim, Adlina; Ismail, Mohd Mahadee; Mohd Nor, Mohd Sabri (Human Resource Management Academic Research Society, 2022)
Collaborative governance is crucial in determining the success of the management of political violence in a nation. Collaboration in managing political violence explains the relationship among different actors toward achieving the desired goal. Recently, collaborative governance remains one of the challenges for the Bauchi state government. The problem is the inability of the state government to involve relevant stakeholders in the management processes of political violence. These hinder the effectiveness of state government in protecting lives and properties. Therefore, the study aims to explore government collaborative efforts in managing political violence and the theory of collaborative governance was adopted. The study employed a qualitative approach through the case study method. Meanwhile purposive and snowballing sampling techniques are used to identify 17 informants. Data were collected in a face-to-face interview via zoom online meeting. The interview data were analyzed using QSR Nvivo 12.0 based on thematic analysis. The result shows the exclusion of relevant stakeholders in the management process. The results further show that the lack of synergy among the security agencies is also a factor affecting the management. Based on the results, the study recommends the establishment of a collaborative mechanism that will allow the involvement of relevant stakeholders in the management process. Therefore, the study highlighted the key factors hindering collaboration in managing political violence.